Stem cell therapy in animal models of central nervous system (CNS) diseases: therapeutic role, challenges and perspectives (Journal of Advanced Veterinary and Animal Research, 2014)
Many human diseases relating to central nervous system (CNS) are mimicked in animal models to evaluate the efficacy of stem cell therapy. The therapeutic role of stem cells in animal models of CNS diseases include replacement of diseased or degenerated neuron, oligodendrocytes or astrocytes with healthy ones, secretion of neurotrophic factors and delivery of therapeutics/genes. Scaffolds can be utilized for delivering stem cells in brain. Sustained delivery of stem cells, lineage specific differentiation, and enhanced neuronal network integration are the hallmarks of scaffold mediated stem cell delivery in CNS diseases. This review discusses the therapeutic role, challenges and future perspectives of stem cell therapy in animal models of CNS diseases.DOI: http://dx.doi.org/10.5455/javar.2014.a17J. Adv. Vet. Anim. Res., 1(3): 75-85, September 2014